Bacillus induced to biosynthesize VOCs & nitriles may benefit agriculture. - Perry, Guenevere; Perry, Diane (PeerJ Preprints, 2019)
The scope of the project was to identify the possible agricultural applications for bacteria induced to synthesize nitriles and VOCs. The study was randomized. Cucurbit seeds and Bacillus licheniformis were selected as the plant and microbial models for two trial studies. In trial 1, 90 cucumber seeds were cultured with B.licheniformis induced to synthesize VOCs (including ethanol, 3-methyl-1-butanol, pentanol), esters (ethyl acetate), and acetonitriles. After 2 weeks the induced bacteria increased seed germination by 68% compared to control samples. Several seedlings were transferred to a small garden, infested with soil nematodes. Roots of control and induced samples appeared affected. Control samples appeared stunted in growth with decreased productivity, but cucumber plants initially planted with induced bacteria were noticeably larger in size with good productivity. Induced Bacillus increased the number of blossoms and cucumber per plant by 125% compared to control samples. Induced Bacillus did not increase solubility of nitrogen, phosphorous, or potassium in the soil, but appeared to increase plant health and defenses against pathogenic infections. Though the study findings are preliminary, soil microbes induced to synthesize VOCs and nitriles may improve plant health and productivity in cucurbit plants.
Keywords: Germination; CROPS; SEEDS; PRODUCTIVITY; PLANTS; BACILLUS; BACTERIA; ETHANOL; FLOWERS; CUCUMBER